Impact measurement in venture philanthropy organizationsː A single case study - Anna Katharina Hochstädter (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2017)
Purpose - This paper investigates the impact measurement needs and practices of a leading venture philanthropy organization (VPO). Methodology - Single case study based on document analysis and semi-structured interviews. Findings - The analyzed VPO does not only seek a certain type of data but also a certain quality to support its pipeline and portfolio management as well as its stakeholder communication. Given the investees' early development stage and the significant challenges in reaching the 'evaluation ideal', the VPO's elaborate impact measurement methodology appears to serve more as a guidepost for where the journey should eventually lead rather than a rigid specification, however. The research also unfolds critical issues surrounding attribution, deadweight, and standardization, which make it difficult for VPOs to reliably account for their own impact at the investment and portfolio levels. Lastly, this work gives rise to the assumption that the VPO-investee relationship is better explained by stewardship than agency theory as suggested by prior research. Research limitations - The restriction to a single VPO presents a material challenge to the generalizability of the findings. Future research should thus test the findings for a larger sample. Practical implications - This work informs (potential) investees why (VP) funders may require certain data and how this can support mission achievement, and (VP) funders how others practice impact measurement and deal with its challenges. Originality/value - This work provides new insights into the hitherto underinvestigated VPO-investee relationship. Specifically, it answers calls for research on the impact measurement needs and practices of (VP) funders.
Keywords: 330; Impact measurement; social performance measurement; social venture capital; venture philanthropy